Blooper and Popular: Creative Brand Publicity Strategy of Head & Shoulders - Putri , Savira Nurindra; Syarifa, Nabila; Hadinugroho, Farid (Jobmark: Journal of Branding and Marketing Communication, 2026)
This article focuses on public discourse and media coverage related to the Creative Brand Publicity (CBP) strategy implemented by Head & Shoulders Indonesia. The strategy, featuring bloopers with the famous actor Joe Taslim, is a key element in creating a connection with the audience. Using a case study method and Wijaya's Creative Brand Publicity theory approach, this study observes and analyzes digital texts related to aspects of mood, moment, movement, and public and media audience conversations. The innovative CBP strategy, as applied by Head & Shoulders, increases brand awareness and consumer engagement and gains extensive publicity, virality, public enthusiasm, and word-of-mouth. These bloopers have garnered significant attention with millions of views on YouTube, creating entertaining and memorable content. The positive response to the program's creativity demonstrates the effectiveness of CBP in building emotional connections with consumers and strengthening brand image. The CBP strategy employed through Joe Taslim's Head & Shoulders bloopers successfully leverages humor and authenticity to create strong emotional connections and enhance brand relatability. This approach increases organic audience engagement and reinforces the brand's image as genuine and approachable, leading to sustained consumer loyalty.